Analisis Penerimaan Pengguna Learning Management System Menggunakan Model UTAUT - Hutabarat, Benedika Ferdian (Prodi Sistem Informasi FST Universitas Jambi, 2020)
E-learning is emerging as an important strategy for providing broad and easy access to high quality education. In Indonesia, the concept of e-learning is usually applied in universities to support learning activities and student administration. This study aims to analyze the factors that affect the level of satisfaction by adopting the UTAUT (Unified Theory of Acceptance and Use of Technology) model and seeing the effect of user satisfaction. by intending to continue to use a new technology (e-learning). The UTAUT model was adopted in this study because it has a useful measurement tool for policy makers to assess the likelihood of the successful introduction of new technology. A quantitative research approach with a survey method is used to determine the factors that affect user satisfaction and the intention to use. The quantitative analysis of survey data was carried out using statistical techniques Partial Least Square Structural Equation Modeling (PLS-SEM) and utilizing SmartPLS 3.2.4 software. In this study, two factors were identified that affect user satisfaction, namely effort expectancy. Furthermore, user satisfaction affects intention to use. Keywords: e-learning, UTAUT, user satisfaction, intention to use, PLS-SEM